Mensch und Computer 2015 - Workshopband Humans and Computers 2015 - Workshop - Schmidt, Albrecht (Mensch & Computer - Tagungsbände / Proceedings, 2015)
The Workshop Volume from the Humans and Computers Conference documents the advanced tutorials that were presented to deepen the understanding gained from the conference lectures. It presents case studies along with accompanying exercises.